CdTe quantum dots precipitation of monodisperse fractions from colloid solutions - Savchuk, O.A.; Trishchuk, L.I.; Mazarchuk, I.A.; Tomashik, V.M.; Tomashik, Z.F.; Dimitriev, O.P.; Boruk, S.D.; Kapush, D.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
CdTe nanocrystals were prepared in aqueous solution by the reaction between Cd²⁺ and H₂Te, obtained electrochemically in a galvanostatic cell, in the presence of thioglycolic acid. Subsequently, we have investigated precipitation of monodisperse fractions of CdTe quantum dots from polydisperse colloid solutions. In addition, the photoluminescence characteristics of these systems were studied in detail.